Identifying Informational Sources And Educational Methods For Soil Conservation Information Used By Landowners of Highly Erodible Fields - Julia A. Gamon; Lahcen Bounaga; W. Wade Miller (Journal of Applied Communications, 1992)
Inadequate adoption of soil conservation practices is a serious problem since 40 percent of the nation's farmers have some highly erodible land.